2022
DOI: 10.1073/pnas.2200514119
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical clouds key to Southern Ocean teleconnections to the tropical Pacific

Abstract: Excessive precipitation over the southeastern tropical Pacific is a major common bias that persists through generations of global climate models. While recent studies suggest an overly warm Southern Ocean as the cause, models disagree on the quantitative importance of this remote mechanism in light of ocean circulation feedback. Here, using a multimodel experiment in which the Southern Ocean is radiatively cooled, we show a teleconnection from the Southern Ocean to the tropical Pacific that is mediated by a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 69 publications
1
49
0
Order By: Relevance
“…In addition, we did the same analysis using a different wind and SST analysis, which produced similar patterns ( SI Appendix ). This SST response is similar in shape to the SST response found in the SO cooling experiments ( 23 , 27 ). These results are subject to uncertainty, and the mechanisms need to be investigated in a series of carefully controlled modeling experiments, but the weight of evidence from observations and model experiments suggests that some significant part of the cooling in the eastern tropical Pacific may be triggered by westerly wind accelerations associated with the Antarctic ozone hole.…”
Section: The Sam and Sstsupporting
confidence: 78%
See 3 more Smart Citations
“…In addition, we did the same analysis using a different wind and SST analysis, which produced similar patterns ( SI Appendix ). This SST response is similar in shape to the SST response found in the SO cooling experiments ( 23 , 27 ). These results are subject to uncertainty, and the mechanisms need to be investigated in a series of carefully controlled modeling experiments, but the weight of evidence from observations and model experiments suggests that some significant part of the cooling in the eastern tropical Pacific may be triggered by westerly wind accelerations associated with the Antarctic ozone hole.…”
Section: The Sam and Sstsupporting
confidence: 78%
“…These experiments on the effect of cloud reflection in the SO on climate resulted in a subprogram under the Climate Modeling Intercomparison Project in which a number of different climate models were subjected to the same reduction in absorbed solar radiation over the SO ( 26 ). Comparison among these models and with observations showed that models with a strong low-cloud feedback could transmit the cooling signal from the SO to the tropics, and that the models with a stronger low-cloud feedback were in better agreement with observed low-cloud behavior ( 27 ). The efficient movement of the cooling signal from the SO to the tropics involves interactions between SST, low clouds, atmospheric circulation, and ocean currents.…”
Section: Recent Work Connecting the So To The Tropical Pacificmentioning
confidence: 83%
See 2 more Smart Citations
“…(2019)). This remains plausible, though its relevance for lower latitude SST trends depends on an active body of work to quantify the teleconnections from Southern Ocean SST changes (Dong et al., 2022; Hwang et al., 2017; Kang et al., 2019; Kim et al., 2022; X. Zhang et al., 2021). Furthermore, there are several mechanisms for how recent Southern Ocean cooling and sea ice expansion could result from anthropogenic forcing, including wind shifts due to a combination of greenhouse gas and ozone forcing (Kostov et al., 2018; Thompson et al., 2011) and increased surface stratification resulting from precipitation changes and/or ice‐sheet melt (Bintanja et al., 2013; De Lavergne et al., 2014; Pauling et al., 2016; Purich et al., 2018), the latter of which is not included in CMIP models.…”
Section: Summary and Discussionmentioning
confidence: 99%